2016
DOI: 10.1016/j.biomaterials.2016.01.055
|View full text |Cite
|
Sign up to set email alerts
|

The AGMA1 poly(amidoamine) inhibits the infectivity of herpes simplex virus in cell lines, in human cervicovaginal histocultures, and in vaginally infected mice

Abstract: a b s t r a c tThe development of topical microbicides is a valid approach to protect the genital mucosa from sexually transmitted infections that cannot be contained with effective vaccination, like HSV and HIV infections. A suitable target of microbicides is the interaction between viral proteins and cell surface heparan sulfate proteoglycans (HSPGs). AGMA1 is a prevailingly cationic agmatine-containing polyamidoamine polymer previously shown to inhibit HSPGs dependent viruses, including HSV-1, HSV-2, and HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 73 publications
1
34
0
Order By: Relevance
“…The AGMA1 activity against HSV-1 and HSV-2 infection was also ascertained on reconstructed human epithelia, namely ectocervico-vaginal tissue (EpiVaginal™), without eliciting inflammation. The same inhibitory effect and lack of inflammatory activity was subsequently confirmed in vivo after topical administration to female mice [141]. Moreover, AGMA1 did not influence the vaginal pH, since proved inactive towards Lactobacillus spp.…”
Section: Paas With Antiviral Activitysupporting
confidence: 52%
See 1 more Smart Citation
“…The AGMA1 activity against HSV-1 and HSV-2 infection was also ascertained on reconstructed human epithelia, namely ectocervico-vaginal tissue (EpiVaginal™), without eliciting inflammation. The same inhibitory effect and lack of inflammatory activity was subsequently confirmed in vivo after topical administration to female mice [141]. Moreover, AGMA1 did not influence the vaginal pH, since proved inactive towards Lactobacillus spp.…”
Section: Paas With Antiviral Activitysupporting
confidence: 52%
“…To confirm this, it was demonstrated that AGMA1 interacts with either immobilized heparin or cellular heparan sulfates, in the latter case preventing HPV attachment to the cell surface [140]. Accordingly, AGMA1 did not kill the virus, but blocked the infection transmission from cell to cell [141].…”
Section: Paas With Antiviral Activitymentioning
confidence: 94%
“…The binding between viruses and HSPGs usually occurs via the interaction of closely-packed arrangements of multiple basic amino acids on the proteins, that constitute the VAL, with the negatively charged sulfated groups of heparan sulfate (HS) in the glycocalix of the cell surface. 9 A long list of HSPG mimicking materials such as heparin, 10,11 sulfated polysaccharides, 9,12 or sulfonic acid decorated polymers, dendrimers, and nanoparticles [13][14][15][16][17] have been tested and shown to exert potent virustatic activity in vitro, none have shown efficacy in humans. The only three polyanionic anti-HIV-1 microbicides that reached phase III clinical trial (i.e.…”
mentioning
confidence: 99%
“…The agmantine-containing poly(amidoamine)s polymer AGMA1 is another interesting microbicide candidate that exerts a multitarget antiviral activity. It binds to HSPG thus preventing the infection of several HSPG-dependent viruses including HSV, HPV and RSV [29][30][31]. Of note, AGMA1 inhibited HSV-2 infection in human cervicovaginal histocultures and significantly reduced the burden of HSV-2 infection in vaginally infected mice [29] …”
Section: Introductionmentioning
confidence: 99%